A CULTURAL EVOLUTIONARY APPROACH TO MODERNITY: WHAT MIGHT IT MEAN FOR CHRISTIAN FAITH?. Issue 1 (19th February 2020) - Patterson, Colin
Abstract: This essay introduces, for theological consideration, some recent work in the field of cultural evolutionary theory, specifically the kin‐influence hypothesis. This theory holds that, following the beginnings of industrialization and economic growth, a nation's fertility rate commences a decline, which is further abetted by the consequent and increasing imbalance in the relative influence of kin versus nonkin influences on individuals in favor of the latter. It is further proposed that this process is itself a major independent factor in the emergence of many of the features of what is called modernity, among which is that of secularization. Extending further this work, I argue that, given the historic alignment of family and religious values in Christian nations, a loss of religious belief and practice is, at least in part, the spill over effect of the opposing influence of values emerging from ever more dominant nonfamily social interaction. I conclude with some reflections on possible theological implications.